2022
DOI: 10.7758/rsf.2022.8.3.02
|View full text |Cite
|
Sign up to set email alerts
|

Rural Food Insecurity: A Longitudinal Analysis of Low-Income Rural Households with Children in the South

Abstract: Dr. SinikkaElliott was a coauthor on this article and co-led the study on which it is based. Sinikka passed away in May 2021, before the article was accepted. Sinikka cared deeply about using research to reduce inequality, confront injustice, and make the world a better place. We are grateful for the chance to have collaborated closely with Sinikka on this article and over the past decade, and we mourn the loss of our colleague and friend. The data analyzed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 47 publications
1
14
1
Order By: Relevance
“…Texas' stringent eligibility requirements and low levels of benefits (the average SNAP recipient in Texas receives less than $3 per person per meal) made it impossible to survive even for mothers who received public food assistance. Sixty‐eight percent of the mothers we interviewed were receiving SNAP; yet, more than half of our sample was food insecure, and 30% were categorized as “very food insecure,” meaning that they skipped meals, ate smaller portions to save food for their children, or went hungry (Bowen et al, 2022). When asked if her benefits were enough, June, a 37‐year‐old single mother of 4 said, “No, it's not enough, nobody, nobody's benefits are enough, no matter who you are, it's not enough, 'cause it's just, it's not enough.” Sylvia, who was married with one child, was recently pushed to find better food management strategies after a bout of food insecurity: “I had to learn just speakin' to other individuals or finding out other resources to … to make sure that [I] survive.” As women who had experienced going without, survival was not taken for granted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Texas' stringent eligibility requirements and low levels of benefits (the average SNAP recipient in Texas receives less than $3 per person per meal) made it impossible to survive even for mothers who received public food assistance. Sixty‐eight percent of the mothers we interviewed were receiving SNAP; yet, more than half of our sample was food insecure, and 30% were categorized as “very food insecure,” meaning that they skipped meals, ate smaller portions to save food for their children, or went hungry (Bowen et al, 2022). When asked if her benefits were enough, June, a 37‐year‐old single mother of 4 said, “No, it's not enough, nobody, nobody's benefits are enough, no matter who you are, it's not enough, 'cause it's just, it's not enough.” Sylvia, who was married with one child, was recently pushed to find better food management strategies after a bout of food insecurity: “I had to learn just speakin' to other individuals or finding out other resources to … to make sure that [I] survive.” As women who had experienced going without, survival was not taken for granted.…”
Section: Resultsmentioning
confidence: 99%
“…She emphasized that mothers should "put yourself last, and let the kids go first." When food was limited, mothers reported skipping and diluting meals to share food with children who lacked (Bowen et al, 2022). Their willingness to offer mothering to non-biological children is indicative of a culturally enshrined belief in mothering as a communal responsibility and effort (Collins, 2005).…”
Section: Grandmothers As Invisible Caregiversmentioning
confidence: 99%
“…Several respondents reported that the lack of a car or mechanical breakdowns were responsible for them losing their jobs (Miller and Edin 2022, this volume, issue 4;Bowen, Elliott, and Hardison-Moody 2022, this volume, issue 3). Greater distances to public services also triggered housing instability, such as that of the family forced to move to an urban area to access necessary medical care (Bowen, Elliott, and Hardison-Moody 2022). Rural social norms and civic and religious institutions can also amplify some of the harmful effects associated with family instability.…”
Section: Consequences On Economic Outcomesmentioning
confidence: 99%
“…Social connections may also matter more in rural areas creating sizable inequalities in how drug charges are handled in the legal system and poor children are perceived in their schools (Brant 2022;Miller and Edin 2022;Sherman and Schafft 2022). Lastly, rural norms valorizing work and independence may make poor rural families, including those experiencing food insecurity, less likely to access government or private assistance (Bowen, Elliott, and Hardison-Moody 2022). These differences compel scholars of child poverty to think about whether policies and programs designed primarily to meet the needs of urban children living in poverty are applicable in rural areas or whether new policies are required.…”
Section: Consequences On Economic Outcomesmentioning
confidence: 99%
“…Support networks are especially important for individuals living in rural areas [ 23 , 24 ]. Living in a rural community shapes the resources and support that families draw upon to navigate their experiences through a variety of challenges, including food insecurity [ 25 ]. The burden of transportation, low vehicle ownership, and distance to healthy, affordable food increases the burden on rural households and creates “inflexible tradeoffs with other household purchases, such as food” [ 26 ] (p. 87).…”
Section: Introductionmentioning
confidence: 99%